Uji Psikometri Skala Cyberstalking Versi Indonesia: Confimatory Factor Analysis dan Invariansi Gender - Sinandang, Rerepih Julung Merekah Wanodya; Pratiwi, Ratri (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2025)
The Cyberstalking Scale has been used in various countries to measure cyberstalking behavior that is increasingly widespread in society, but there is no research that examines the psychometric properties of the Cyberstalking Scale in Indonesia. This study aims to look at the psychometric properties of construct validity with CFA and gender measurement invariance of the Indonesian version of the Cyberstalking Scale. Participants consisted of 306 male and female respondents aged 18-22 years who actively play social media. Respondents were selected using purposive sampling technique. Evaluation of the internal structure validity of the Indonesian version of the Cyberstalking Scale includes factor structure, composite reliability, and measurement invariance between genders tested using confirmatory factor analysis, reliability, and confirmatory multigroup factor analysis. The results show that the cyberstalking scale is valid and reliable (α = 0.922) In addition, the cyberstalking scale is also invariant at the strict stage.